2017
DOI: 10.1017/etds.2016.133
|View full text |Cite
|
Sign up to set email alerts
|

Topology and convexity in the space of actions modulo weak equivalence

Abstract: We analyse the structure of the quotient A∼(Γ, X, µ) of the space of measure-preserving actions of a countable discrete group by the relation of weak equivalence. This space carries a natural operation of convex combination. We introduce a variant of an abstract construction of Fritz which encapsulates the convex combination operation on A∼(Γ, X, µ). This formalism allows us to define the geometric notion of an extreme point. We also discuss a topology on A∼(Γ, X, µ) due to Abert and Elek in which it is Polish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…In [T-D1, Theorem 5.1] it is shown that if we transfer the relative topology of this subset back to A ( , X, µ) via this bijection, we obtain a compact, metrizable topology on A ( , X, µ). It was shown in [Bu,Theorem 3.1] that this coincides with the topology defined before.…”
supporting
confidence: 72%
See 3 more Smart Citations
“…In [T-D1, Theorem 5.1] it is shown that if we transfer the relative topology of this subset back to A ( , X, µ) via this bijection, we obtain a compact, metrizable topology on A ( , X, µ). It was shown in [Bu,Theorem 3.1] that this coincides with the topology defined before.…”
supporting
confidence: 72%
“…THEOREM 9.3. [Bu,Proposition 5.1]; see also [T-D1, Theorem 1.8], and [E,Theorem 9] If is amenable, then a b ⇐⇒ type(a) = type(b).…”
Section: Invariant Random Subgroupsmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper also establishes equivalent definitions of weak containment in terms of the space of all actions and ultraproducts of actions. this result inspired us to finish this work[Bur15]. So thanks, Peter.…”
mentioning
confidence: 77%